2011
DOI: 10.1097/aog.0b013e3182179e28
|View full text |Cite
|
Sign up to set email alerts
|

Term Pregnancy

Abstract: Objective Term pregnancy (37–41 weeks of gestation) is generally regarded as a uniform period for pregnancy outcome. The purpose of this study was to estimate the trend of maternal racial/ethnic differences in mortality for early term (37 0/7 – 38 6/7 weeks of gestation) compared to full term births (39 0/7 – 41 6/7 weeks of gestation). Methods We analyzed 46,329,018 singleton live births using the National Center for Health Statistics (NCHS) U.S. period-linked birth/infant death data from 1995 to 2006. Infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(61 citation statements)
references
References 12 publications
3
56
2
Order By: Relevance
“…In particular, non-Hispanic black women have elevated risks of both stillbirth and infant death, with rates of both more than double that seen in non-Hispanic whites (1-3). Hispanic and Asian women have rates of stillbirth similar to non-Hispanic white women with lower rates of infant death (2-5). Although complications of preterm delivery do play a large role in some of these disparities, 29% of all stillbirths after 24 weeks and 63% of infant deaths occur in term pregnancies, with similar rates of disparities seen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, non-Hispanic black women have elevated risks of both stillbirth and infant death, with rates of both more than double that seen in non-Hispanic whites (1-3). Hispanic and Asian women have rates of stillbirth similar to non-Hispanic white women with lower rates of infant death (2-5). Although complications of preterm delivery do play a large role in some of these disparities, 29% of all stillbirths after 24 weeks and 63% of infant deaths occur in term pregnancies, with similar rates of disparities seen.…”
Section: Introductionmentioning
confidence: 99%
“…Although complications of preterm delivery do play a large role in some of these disparities, 29% of all stillbirths after 24 weeks and 63% of infant deaths occur in term pregnancies, with similar rates of disparities seen. (2, 4, 5)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, term infants born at 37 to 42 weeks have been considered a uniform group 31. However, more recently, early‐term infant vulnerability has been documented and several studies in infants without CCHD have shown that early‐term infants born at 37 to 38 weeks have a higher incidence of respiratory distress, developmental morbidities, and even infant mortality 32, 33. In infants with CCHD, 2 studies have shown increased mortality, neonatal morbidities, and postoperative complications in early‐term versus full‐term infants 7, 8.…”
Section: Discussionmentioning
confidence: 99%
“…We lacked the power to assess this issue and other data suggest that neonatal, postneonatal and infant mortality may be increased with early term compared with full-term delivery. 10 …”
Section: Commentmentioning
confidence: 99%